On the spectral Green’s function-constant nodal method for fixed-source SN problems in X,Y-geometry with arbitrary L’th-order anisotropic scattering - Welton Menezes; Gustavo Alvarez; Ricardo Barros (Brazilian Journal of Radiation Sciences)
Presented here is an extension of the spectral Green’s function-constant nodal (SGF-CN) method for the numerical solution of energy multigroup, fixed-source, discrete ordinates (SN) problems in X, Y-geometry with arbitrary L’th-order of scattering anisotropy, provided L<N. This analytical coarse-mesh method uses the multigroup SGF method for numerically solving the one-dimensional transverse-integrated SN nodal equations with constant approximations for the transverse leakage terms. The only approximations in the present version of the SGF-CN method occur in these transverse leakage terms, as the energy-group transfer scattering source terms are treated analytically within the offered method. Numerical results to typical model problems are given to illustrate the method’s accuracy and to analyze the efficiency of the offered SGF-CN computer code for neutral particle transport calculations.